Voices of madness in Foucault and Kierkegaard - Ohaneson, Heather C. (International journal for philosophy of religion, 2020)
The central idea of this paper is that Michel Foucault and Søren Kierkegaard are unexpected allies in the investigation into the relation between madness and reason. These thinkers criticize reason's presumption of purity and call into question reason's isolation from madness. Strategies of indirect communication and regard for paradox from Kierkegaard's nineteenth-century works find new ground in Foucault's twentieth-century archaeological undertaking as Foucault illuminates "both-and" moments in the history of madness, uncovering points where rationalism paradoxically conceives of madness or where madness is not unreasonable. Furthermore, for both thinkers, form and content meet, as Kierkegaard and Foucault's occasionally "delirious lyricism" (in the phrase of Dominick LaCapra) exemplifies the intertwining of logical and illogical forces.